2012
DOI: 10.1038/cdd.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of the RanBP9-cofilin pathway in Aβ-induced apoptosis and neurodegeneration

Abstract: Neurodegeneration associated with amyloid b (Ab) peptide accumulation, synaptic loss, neuroinflammation, tauopathy, and memory impairments encompass the pathophysiological features of Alzheimer's disease (AD). We previously reported that the scaffolding protein RanBP9, which is overall increased in brains of AD patients, simultaneously promotes Ab generation and focal adhesion disruption by accelerating the endocytosis of amyloid precursor protein (APP) and b1-integrin, respectively. Here, we show that RanBP9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(116 citation statements)
references
References 27 publications
9
106
1
Order By: Relevance
“…Consistent with this prediction, here we found increased levels of both RanBP9-FL and RanBP9-N60 in Alzheimer's brains as well as AP⌬E9 transgenic mice. We also demonstrated previously that RanBP9 protein levels were increased in J20 mice, also APP transgenic mice (37). We also demonstrated that RanBP9 scaffolds a tripartite protein complex by directly binding to LRP, APP, and BACE1, and enhances their interaction and A␤ generation (10,11).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consistent with this prediction, here we found increased levels of both RanBP9-FL and RanBP9-N60 in Alzheimer's brains as well as AP⌬E9 transgenic mice. We also demonstrated previously that RanBP9 protein levels were increased in J20 mice, also APP transgenic mice (37). We also demonstrated that RanBP9 scaffolds a tripartite protein complex by directly binding to LRP, APP, and BACE1, and enhances their interaction and A␤ generation (10,11).…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, we have now demonstrated that COPS5 can also bind with APP, LRP, and BACE1. Further, RanBP9 accelerates endocytosis of APP, LRP, and ␤1-integrin by physically interacting with each one of them, thereby simultaneously regulating cell adhesion and A␤ generation (11,37). Because endocytosis of APP and LRP is required for A␤ generation (38 -40), COPS5-mediated increased A␤ generation may be the consequence of increased RanBP9 protein levels and APP/LRP endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased RanBP9 protein levels in AP⌬E9/ COPS5 mice were almost double the quantity seen in COPS5-Tg mice. This is consistent with our previous observation that RanBP9 protein levels are increased in both J20 (22) and AP⌬E9 (27) mouse brains compared with littermate controls. The exact reason for an increase in RanBP9 levels under APP overexpression conditions is not known, but such an increase was confirmed in the AD brains as well (23,27,31).…”
Section: Volume 290 • Number 14 • April 3 2015supporting
confidence: 93%
“…In a recent study, RanBP9 has been found to be within the clusters of RNA transcript pairs associated with markers of AD progression (18), suggesting that RanBP9 might contribute to the pathogenesis of AD. In fact, we demonstrated previously that RanBP9 is an important component of a multiprotein complex involving LRP, BACE1, and APP that robustly increased A␤ levels (19,20) and substantially reduced synaptic proteins (21)(22)(23)(24)(25) because of reduced dendritic intersections and spine density (26), consequently leading to severe deficits in learning and memory performance in AP⌬E9 mice overexpressing RanBP9 (23,25). We also recently identified COP9 constitutive photomorphogenic homolog subunit 5 (COPS5, Jab1) as a bona fide binding partner of RanBP9 (27).…”
mentioning
confidence: 99%
“…siRNA knockdown of cofilin abolished both A␤ and RanBP9-induced apoptosis (122). In hippocampal neurons, fibrillar A␤ was able to alter the PAK1/LIMK1/cofilin axis and thereby actin organization (123).…”
Section: Fig 7 Western Blot Analysis Of S-nitrosylated Proteins Fromentioning
confidence: 99%